PERLINDUNGAN HAK CIPTA MOTIF TENUN ENDEK DAN SONGKET DI DESA TELAGATAWANG - A A I Agung Maheswari; Ni Made Gitariani; Dewa Ayu Yeni Asmari; I Gede Suastika (Universitas Muhammadiyah Tapanuli Selatan, 2020)
Weaving is one of the cultural heritage, which is the pride and identity of the Indonesian people. One of the villages where the people make the most money from weaving is Telagatawang Village, Kec. Sidemen, Karangasem. The rise of counterfeiting, piracy, due to unfair competition between employers or artisans indeed lead to conflict and losses for other parties. The issue of legal protection (Copyright) in the field of trade or business is necessary. Therefore the author will discuss